2011
DOI: 10.1073/pnas.1100473108
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dispersal allows an upstream region to control population structure throughout a species’ range

Abstract: In a single well-mixed population, equally abundant neutral alleles are equally likely to persist. However, in spatially complex populations structured by an asymmetric dispersal mechanism, such as a coastal population where larvae are predominantly moved downstream by currents, the eventual frequency of neutral haplotypes will depend on their initial spatial location. In our study of the progression of two spatially separate, genetically distinct introductions of the European green crab (Carcinus maenas) alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
128
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(142 citation statements)
references
References 28 publications
13
128
1
Order By: Relevance
“…Compared to other systems , the unidirectional flow in the NGC greatly simplifies the identification of source populations, for instance, within a 100 km window capturing demographic connectivity for summer spawners. In such an asymmetric system, upstream populations are predicted to drive patterns of genetic structure throughout the entire area (Pringle et al 2011) and are thus critical for population viability and evolutionary adaptation. Our estimates of genetic connectivity suggest overall uninterrupted gene flow among sampled localities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other systems , the unidirectional flow in the NGC greatly simplifies the identification of source populations, for instance, within a 100 km window capturing demographic connectivity for summer spawners. In such an asymmetric system, upstream populations are predicted to drive patterns of genetic structure throughout the entire area (Pringle et al 2011) and are thus critical for population viability and evolutionary adaptation. Our estimates of genetic connectivity suggest overall uninterrupted gene flow among sampled localities.…”
Section: Discussionmentioning
confidence: 99%
“…Plantas e invertebrados. FAO, Rome Pringle JM, Blakeslee AMH, Byers JE, Roman J (2011) Asymmetric dispersal allows an upstream region to control population structure throughout a species' range. Proc Natl Acad Sci USA 108: 15288−15293 Pritchard JK, Stephens M, Donnelly P (2000) Inference of population structure using multilocus genotype data.…”
mentioning
confidence: 99%
“…Genetic analysis revealed that this rapid northward expansion was concurrent with a second introduction of the species from northern Europe (Roman, 2006). Since that time, the two introduced populations have widely introgressed, with genetic signatures of the original invasion extending throughout the East Coast range, and signatures of the second introduction extending as far south as New York and still moving southward (Pringle et al, 2011). In contrast, the West Coast population was founded circa 1990 by individuals from the original East Coast introduction, and by 1998 had spread to its current distribution between Elkhorn Slough, CA, USA, and Vancouver Island, BC, Canada, with no evidence for multiple introductions (Behrens Yamada et al, 2005;Tepolt et al, 2009).…”
Section: Research Articlementioning
confidence: 99%
“…2011), or those with strong habitat quality gradients, which can lead to competition‐driven directional dispersal (Paz‐Vinas et al. 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2011). For example, when aiming to conserve endangered species, implementing management strategies for source populations is known to be more effective than for sink populations (Dias 1996).…”
Section: Introductionmentioning
confidence: 99%